(untitled) (Journal of Human Sciences, 2022)
The current study aims to identify the factors affecting the spread of crime in the Libyan south, from the point of view of a sample of community members in the city of Sebha, where the research problem is summarized in the following main question: What are the factors affecting the spread of crime in the Libyan south in the city of Sebha? A random sample of (80) individuals from the community of Sebha city were chosen randomly, using the descriptive approach, and after verifying the validity and stability of the study tool, the study’s questions were answered through the use of appropriate statistical methods, the arithmetic mean, standard deviation and relative weight were used. Dimensions and expressions of the factors affecting the spread of crime in the Libyan south. The results of the study showed the following: 1- The most influential factors in the spread of crime in the south of Libya, respectively, are (economic factors, psychological factors, family factors, social factors, and then religious and cultural factors). 2- The sample members indicated that the most economic factors were in a row (crime spreads due to the increase in material burdens, harsh material conditions of life, and the inability to meet basic needs). 3- The sample members indicated that the most psychological factors were in a row (crime spreads due to drug addiction, and the spread of deviant behaviors). 4- The sample members indicated that the most family factors affecting the spread of crime, respectively, are (crime spreads due to parents’ neglect and lack of follow-up to their children, as well as because of deprivation and emotional neglect by parents towards their children, and the low cultural level of parents). 5- The sample members indicated that the most social factors affecting the spread of crime, respectively, are: (crime spreads due to bad company, the surrounding environment associated with crime, and the lack of places for entertainment and entertainment in the environment). 6- The sample members indicated that the most religious and cultural factors affecting the spread of crime, respectively, are: (weak religious and moral awareness, security chaos and the spread of weapons, and weak social control institutions.